Small‐Fiber Degeneration in Alcohol‐Related Peripheral Neuropathy - Mellion, Michelle L.; Silbermann, Elizabeth; Gilchrist, James M.; Machan, Jason T.; Leggio, Lorenzo; Monte, Suzanne (Alcoholism, clinical and experimental research, 2014)
Background Alcohol‐related peripheral neuropathy (ALN) is generally characterized as an axonal large‐fiber polyneuropathy caused by thiamine deficiency. We hypothesized, based on clinical observations, that ALN is associated with a small‐fiber polyneuropathy that can be diagnosed with skin biopsy in heavy alcohol drinking subjects with normal thiamine status. Methods Eighteen individuals (9 heavy alcohol drinking subjects and 9 healthy control subjects) were assessed for the potential utility of skin biopsies in detecting ALN‐associated small nerve fiber degeneration. Heavy drinking was defined as greater than 4 drinks/d and 5 drinks/d in women and men, respectively, as determined by the Timeline Follow‐Back and lifetime drinking history. All subjects underwent neurological examination, nerve conduction studies, and skin biopsies to quantify end nerve fiber densities (ENFD). Other causes of neuropathy were excluded and thiamine status was assessed. Results Average ENFD were significantly decreased at the calf in the alcohol group as compared with control group (p < 0.0001). Histological sections demonstrated striking attrition and architectural simplification of intraepidermal nerve fibers in the heavy alcohol drinking subjects. There were no significant intergroup differences with respect to clinical assessments of neuropathy or thiamine status. Conclusions ALN is associated with a small‐fiber neuropathy that can be detected with skin biopsy in heavy alcohol drinking individuals with normal thiamine status. Skin biopsy is a useful, minimally invasive biomarker that could extend studies to understand the effect of alcohol on the peripheral nerves and to evaluate potential therapeutic agents in larger clinical trials.